Qualitative perspectives of new graduate nurses to educational preparation for patient care - Vilma Ajijul Jana; Teh Halimatun Radizuan; Gemalyn S Maldisa (Program Studi Ilmu Keperawata Fakultas Kedokteran Universitas Malahayati Bandar Lampung, 2023)
Background: A phenomenological qualitative study were conducted and investigated the perceptions of new Nursing graduates in relation to their educational preparation in caring for patients. Practice readiness and preparedness of new nurses continue to be a challenge in 21st century healthcare delivery system. To adapt to the rapidly varying and advancing healthcare settings; nurse educators must regularly assess and review education curricula, teaching-learning strategies and programs adopted to prepare new professional nurses. In Malaysia, Nursing Education Task Force was formed– Ministry of Higher Education (MOHE), 2010. ‘Development of Nursing Education in Malaysia towards the year 2020’. The aim of this task force is to improve and transform Nursing Education in Malaysia from Diploma to degree programmes by the year 2020, to prepare New Nurses to practice in all priority areas of nursing care.Purpose: To explore and describe the experiences of new graduate nurses working in hospitals and their perceptions in relation to educational preparation for patient care.Method: Using a Phenomenological Qualitative study, This Study focused on the lived and expressed experiences of the participants. It involved the description and interpretation of human experiences so that the experience could be better understood.Results: Seven Themes were extracted from the significant statements and formulated meanings of the ten respondents who voluntarily participated in this study. Orientation process, Value of preceptor, Solidifying concepts, Knowledge, Role transition, Doctors’ behaviour towards new staff and Staff shortage were among the needs of the new graduate Nurses that needs to be addressed.Conclusion: This study was able to provide insights into the lived experiences of ten new nurses and their perceptions in relation to educational preparations for patient care. Recommendations were also made to meet and support the new nurses’ needs. These findings, which may have important implications for nursing practice, management, education and to nursing profession as a whole, need further study in a larger scale to explore more on the lived and expressed experiences of the new nurses and to strongly support this research study.